THE PRICING STRATEGY THROUGH VALUE-BASED PRICING STRATEGY OR LOWEST PRICING STRATEGY IN GARUDA INDONESIA BASED ON SMART APPROACH - Norma Aulia; Santi Novani (Sean Institute, 2023)
Garuda Indonesia, a leading player in the aviation industry, is at the heart of this research, focusing on the comparative analysis of its two major pricing strategies, value-based pricing and lowest pricing.This study investigates the effectiveness of value-based pricing and lowest pricing strategies adopted by Garuda Indonesia, employing a SMART (Specific, Measurable, Achievable, Relevant, Time-bound) framework. This comparative evaluation aims to identify the strategy best suited to Garuda Indonesia's current market conditions and business objectives. The research considers diverse data, including company financial records, customer surveys, and comprehensive market analyses, to fully understand the economic, competitive, and consumer-driven factors influencing pricing decisions. Factors such as fluctuating demand and supply, escalating competition, operational costs, and Indonesian consumers' nuanced perception of value are thoroughly examined. By setting precise metrics for success within the SMART framework, the study accurately measures the impact of these pricing strategies on Garuda Indonesia's profitability and competitive standing. The research outcomes will provide critical insights and strategic recommendations for Garuda Indonesia's pricing policy, with potential applications for the broader aviation industry. Ultimately, this study deepens the understanding of pricing strategy dynamics, contributing significantly to academia and industry practice.